2020
DOI: 10.1007/s40735-020-00439-7
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Mild Steel in Acidic Media by N-[(3,4-Dimethoxyphenyl)Methyleneamino]-4-Hydroxy-Benzamide

Abstract: Mild steel (a low carbon steel) is an affordable engineering material used for many purposes in various environments including mild acidic environment with some precautions. The corrosion behaviour of mild steel (MS) in 0.5 M H2SO4 and 0.5 M HCl, in the temperature range (303–323 K) without and with the inhibitor N-[(3,4-dimethoxyphenyl) methyleneamino]-4-hydroxy-benzamide (DMHB), was investigated using Potentiodynamic polarization and Electrochemical impedance spectroscopy (EIS) techniques supplementing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…These differences in weight losses can be referred to the quite aggressive attacks, toward the steel surfaces, by the latter two media than in case of water and formation water. These stronger attacks can be explained by the increased number of corrosive sites in diesel fuel and sulfuric acid compared to those of aqueous media (Muthamma et al 2021). In an agreement with illustrated data in Table 3, the maximum CIE could be noticed, after 10 days, in case of using pure water.…”
Section: Impact Of Corrosion Inhibitor Dosesupporting
confidence: 84%
“…These differences in weight losses can be referred to the quite aggressive attacks, toward the steel surfaces, by the latter two media than in case of water and formation water. These stronger attacks can be explained by the increased number of corrosive sites in diesel fuel and sulfuric acid compared to those of aqueous media (Muthamma et al 2021). In an agreement with illustrated data in Table 3, the maximum CIE could be noticed, after 10 days, in case of using pure water.…”
Section: Impact Of Corrosion Inhibitor Dosesupporting
confidence: 84%
“…Recently, many researchers have reported that nitrogen-containing compounds such as fatty hydrazide and its derivatives demonstrated to be effective inhibitors for metal corrosion in acidic mediums. Their versatile molecular structure containing electron-donating groups, heteroatoms, π-electrons, and lone pair increases their ability to mitigate corrosion in an acidic medium [27]. Besides, the presence of heteroatoms acts as the active adsorption site to form a protection layer on the metal surface and facilitates more donor-acceptor interaction with the inhibitor's molecules [28].…”
Section: Fatty Hydrazides Derivatives As Effective Corrosion Inhibitorsmentioning
confidence: 99%
“…Furthermore, many studies on corrosion inhibitors have found that hydrazides of fatty acids are more efficient inhibitors than cyclic amines, hydrazides, and aromatic amines [29]. Moreover, hydrazide derivatives are well known for their effectiveness as anticancer, antibacterial, anti-inflammatory, analgesic, and antioxidant properties [27,30]. Numerous studies have been conducted using fatty hydrazides as corrosion inhibitors in the past years.…”
Section: Fatty Hydrazides Derivatives As Effective Corrosion Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of the organic compound on metals or alloys is controlled by many factors, such as the surface nature, type of the metal charge, and the inhibitor structure. Among organic compounds, hydrazine compounds showed high corrosion inhibition effectiveness [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Experimental methods are appropriate for clarifying the inhibition mechanisms and the corrosion behaviour of metals and alloys, but they are time-consuming and expensive.…”
Section: Introductionmentioning
confidence: 99%